If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 3) = 2 Reorder the terms: (3 + 7x) = 2 Remove parenthesis around (3 + 7x) 3 + 7x = 2 Solving 3 + 7x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 7x = 2 + -3 Combine like terms: 3 + -3 = 0 0 + 7x = 2 + -3 7x = 2 + -3 Combine like terms: 2 + -3 = -1 7x = -1 Divide each side by '7'. x = -0.1428571429 Simplifying x = -0.1428571429
| 16s+4s=20 | | 9n-37=71 | | 3h-h=10 | | 2(x+9)=20 | | 9m-6m=6 | | 10w-4w=18 | | (x+3y)(3x+y)= | | (1+2w)*w*2w=40 | | -60x^3+144x= | | c/4+85=99 | | 4x+1=6-x | | -4+6s+7m-4s-4m-6= | | 2(13-4x)-9(x+6)= | | 49x^2-91+42=0 | | -8x-(5x+5)=7 | | 2(h-4)=6 | | 3y+7(2y+6)-2+3(4y+9)=270 | | -7x-15=2x-6 | | 12a-11-9a=1 | | 7h-16=54 | | 3x^2+31x+8=0 | | 10=4+2d | | x(-11+x)=0 | | -4x+22=x-8 | | 2h-3=3 | | -40x^2-18x+36=0 | | 1=10-3t | | 22-x=4x-8 | | -8x^2+32x-30=0 | | 2r-4=4 | | 5X^2-66X+1=0 | | 41=15x+(-3)x^2 |